Proof: Do Expr At Unchanged 43
Let's prove the following theorem:
if the following are true:
- expression state at time 43 = "begin_expr"
- the expression at time 43 = self."x" =
__add__(self.x, 5)
then the expression at time 44 = self."x" = __add__(self.x, 5)
Proof:
Given
1 | expression state at time 43 = "begin_expr" |
---|---|
2 | the expression at time 43 = self."x" = __add__(self.x, 5) |
# | Claim | Reason |
---|---|---|
1 | the expression at time (43 + 1) = the expression at time 43 | if expression state at time 43 = "begin_expr", then the expression at time (43 + 1) = the expression at time 43 |
2 | the expression at time (43 + 1) = self."x" = __add__(self.x, 5) |
if the expression at time (43 + 1) = the expression at time 43 and the expression at time 43 = self."x" = __add__(self.x, 5) , then the expression at time (43 + 1) = self."x" = __add__(self.x, 5) |
3 | 43 + 1 = 44 | 43 + 1 = 44 |
4 | the expression at time (43 + 1) = the expression at time 44 | if 43 + 1 = 44, then the expression at time (43 + 1) = the expression at time 44 |
5 | the expression at time 44 = self."x" = __add__(self.x, 5) |
if the expression at time (43 + 1) = the expression at time 44 and the expression at time (43 + 1) = self."x" = __add__(self.x, 5) , then the expression at time 44 = self."x" = __add__(self.x, 5) |
Comments
Please log in to add comments